The Relationship Between Workplace Bullying and Job Stress in Female Blue Collar Workers in Indonesia - Anitasari Kusumawati; Endang Parahyanti; Aria Kekalih; Herqutanto; Dewi Sumaryani Soemarko (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Introduction: Among the many risk factors for stress in the workplace, bullying is a factor that is rarely discussed. As many as 19% of people in America experience bullying at work, followed by other European countries. Bullying is a strong link to worker stress, especially in blue-collar workers. Gender differences, especially in women, also have an important prevalence in workplace bullying. In Indonesia itself, there is no data regarding bullying in the workplace, especially among women and blue-collar workers. Objective: This study aims to find the relationship between bullying and stress in the workplace among female blue-collar workers. Method: This research is a cross-sectional analytical study using a negative act questionnaire-revised (NAQ-R) questionnaire on work stress in female blue collar workers in garment factories, in Bekasi city, Indonesia. Job stress assessment uses the Perceived Stress Scale-10 (PSS-10) questionnaire. Other variables assessed are age, salary, marital status, and subjective questions related to workload and work communication. Results: A total of 379 female blue collar workers in garment factories, in the city of Bekasi, Indonesia took part in this research. Workplace bullying is associated with job stress in female blue-collar workers. Workers who are often bullied tend to have medium-high levels of work stress. Bullying is the type of bullying with the highest scale. Conclusion: Workplace bullying is the factor that has the most influence on work stress in female blue-collar workers. Then, high workloads, poor communication, and lower salaries are related to bullying and stress in the workplace.